2000
DOI: 10.1111/j.1467-842x.2000.tb00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Substance use by Indigenous and non-Indigenous primary school students

Abstract: Objective: Recent Australian research with adolescents aged 13 to 17 years has found that Indigenous youth are more likely than non-Indigenous adolescents to smoke tobacco and cannabis, although they may be less likely to use alcohol. The objective of this study was to examine whether this pattern exists among younger children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Australian research shows similar trends. Aboriginal youth drink significantly less alcohol and drink less frequently than matched non-Aboriginal adolescents (Dunne, Yeo, Keane, & Elkins, 2000; Hennessy & Williams, 2001). However, drinking for Aboriginal youth dramatically increases after age 18, at which point the rates of high-risk drinking surpass those of non-Aboriginal youth (Hennessy & Williams, 2001; Kelly & Kowalyszyn, 2003).…”
Section: Individual Risk Factorsmentioning
confidence: 99%
“…Australian research shows similar trends. Aboriginal youth drink significantly less alcohol and drink less frequently than matched non-Aboriginal adolescents (Dunne, Yeo, Keane, & Elkins, 2000; Hennessy & Williams, 2001). However, drinking for Aboriginal youth dramatically increases after age 18, at which point the rates of high-risk drinking surpass those of non-Aboriginal youth (Hennessy & Williams, 2001; Kelly & Kowalyszyn, 2003).…”
Section: Individual Risk Factorsmentioning
confidence: 99%
“…For example, substance use, stolen generation effects, and others, could be presented (Armstrong, 2002, October;Arnold, 2002, June;Brady, 1991;D'Abbs, Hunter, Reser, & Martin, 1994;Dunne, Yeo, Keane, & Elkins, 2000;Forero, Bauman, Chen, & Flaherty, 1999;Gray & Chikritzhs, 2000;Jones, Masters, Griffiths, & Moulday, 2002;Pelling, 2002;Pelling, 2007;Petchkovsky & San Roque, 2002;Reser, 1991;Sandover, Houghton, & O'Donoghue, 1997;Spencer, 2000;Tan, 1998;Wilson, 2001). While the ability to engage in competent service with Indigenous clients is important, Australian psychologists are not likely to specifically receive training regarding Indigenous populations.…”
Section: Six Important Specific Counselling Psychology Competence Areasmentioning
confidence: 99%
“…Studies that have been conducted with indigenous youth samples have primarily been epidemiological in nature, and have shown that they experience higher rates of substance abuse than majority populations. For example, Okamoto, Kulis, Helm, Edwards, and Giroux (2014) found that Native Hawaiian youth had a significantly higher risk for substance abuse than non-Native Hawaiian youth, while Dunne, Yeo, Keane, and Elkins (2000) found that indigenous Australian adolescents ages 13 to 17 were more likely to abuse substances than non-indigenous youth.…”
Section: Literature Reviewmentioning
confidence: 99%